Edible bird’s nest, an Asian health food supplement, possesses anti-inflammatory responses in restoring the symptoms of atopic dermatitis: An analysis of signaling cascades - Lai, Queenie Wing Sze; Fan, Qunyan; Zheng, Brody Zhongyu; Chen, Yanxian; Dong, Tina Tingxia; Tsim, Karl Wah Keung (Frontiers in Pharmacology, 2022)
Edible bird’s nest (EBN) is a Chinese delicacy possessing skin rejuvenating functions. To verify skin anti-inflammatory function of EBN, water extract and enzymatic digest of EBN, as well as the major sialic acid, N-acetyl neuraminic acid (NANA), were probed in TNF-α-treated HaCaT keratinocytes. The mRNA expressions of pro-inflammatory cytokines, e.g., IL-1β, IL-6, TNF-α, and an enzyme responsible for inflammatory response, i.e., Cox-2, as well as filaggrin and filaggrin-2, were markedly altered after treating with different preparations of EBN. The EBN-mediated responses could be accounted by its robust reduction of reactive oxygen species (ROS), NF-κB signaling and phosphorylation of p38 MAPK and JNK, as triggered by TNF-α-induced inflammation. The anti-inflammatory response of EBN was further supported in animal model. In 2,4-dinitrochlorobenzene (DNCB)-induced dermatitic mice, the effects on skin thickness, severity level of damage and scratching behavior, exerted by DNCB, were reversed after EBN treatments, in dose-dependent manners. In parallel, the levels of immune cells and pro-inflammatory cytokines in dermatitic skin were markedly reduced by treatment of EBN preparations. In general, NANA and enzymatic digest of EBN showed better anti-inflammatory responses in both models of in vitro and in vivo. These lines of evidence therefore suggest the possible application of EBN in treating atopic dermatitis.